Public relations focused on responsibility: A discourse analysis of PR based TED talks (2012-2022) - ÖZGEN, EBRU (My University, 2023)
In this study, our aim is to reveal the importance of public relations focused on responsibility and to analyze how the interrelated concepts of communication, social responsibility and sustainability are handled in TED talks and whether there is a difference in the definitions made in line with today’s changing and developing conditions through content analysis. TED, one of the most prestigious organizations in the world with inspiring speakers and interesting topics, serves as an important channel in terms of understanding and making sense of what has happened in the public relations field in the last 10 years. For this reason, a total of 68 TED talks on the TEDx Talks Youtube channel, 27 on communication, 6 on public relations, 18 on social responsibility and 17 on sustainability, were analyzed in detail via content analysis Each concept was redefined with the key themes emerging from the analyzes. It has been concluded that public relations has become a necessity in conceptualizing that it is a discipline that creates social good and acts with social responsibility, sustainability and universal ethical values. This necessity has been clearly demonstrated in this study.
Keywords: Communication; Public Relations; Social Responsibility; Sustainability; TED Talks